A new relevance and better prospects for wider uptake of social learning within CGIAR - Gonsalves, Julian Francis (2013)
Relying entirely on survey information and personal exchanges with over 70 scientists from within the CGIAR network, this working paper attempts to achieve a better understanding of the scope of social learning related efforts undertaken in CGIAR and main issues of relevance to more current efforts, such as that planned by the CGIAR program on Climate Change Agriculture and Food Security (CCAFS). A wide range of methods was identified, where groups of people learn in order to jointly arrive at solutions to pressing food security problems. This methodological diversity is considered a strength given that they represent the different contexts that the research community is responding to. Relying on experiential evidence from professionals within the CGIAR network, the working paper further explores if the reformed CGIAR and the new structural and programmatic setup offer improved prospects for the inclusion of social learning approaches in CCAFS. A range of working definitions of social learning – from the literature – is proposed to meet the special needs/context of scientists. The stocktaking exercise also attempts to identify what is needed to foster an enabling environment for social learning. Key propositions are derived from the findings of the stocktaking exercise. Relying on secondary information provided by respondents, case overviews of exemplary and mature examples of social learning from within CGIAR were developed with the purpose of highlighting that CGIAR does already have a tradition to build upon in future work. Finally, an illustrative listing of current CGIAR projects provided to support the stocktaking objectives of this effort.